2009
DOI: 10.4161/cib.7714
|View full text |Cite
|
Sign up to set email alerts
|

Within-population genetic variability in mycorrhizal interactions

Abstract: The geographic mosaic theory of coevolution hypothesizes that natural selection on species interactions varies among ecosystems, partly because the genes involved in species interactions differ in their fitness effects among environments. This selection mosaic may be expressed, at the extreme, as ecological outcomes ranging from mutualism to parasitism among environments. In a recent laboratory experiment on the interaction between a plant, bishop pine (Pinus muricata), and a root-symbiotic ectomycorrhizal fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…2004; Piculell et al. 2008; Hoeksema et al. 2009), may have substantial effects on how plants respond to mycorrhizal inoculation, and yet are almost never manipulated explicitly in experiments or reported in publications.…”
Section: Discussionmentioning
confidence: 99%
“…2004; Piculell et al. 2008; Hoeksema et al. 2009), may have substantial effects on how plants respond to mycorrhizal inoculation, and yet are almost never manipulated explicitly in experiments or reported in publications.…”
Section: Discussionmentioning
confidence: 99%
“…), a more northerly coastal species. Using crossinoculation experiments with multiple genotypes of fungi and pines, we found that within populations, fungal and pine seedling performance frequently varied with fungal genotype, pine genotype, and abiotic factors, suggesting the potential for ongoing coevolution (G 3 G interactions) mediated by selection mosaics (G 3 G 3 E interactions) among populations (Piculell et al 2008, Hoeksema et al 2009). We also found evidence for local adaptation of fungal populations to nearby pine populations at a large geographic scale, suggesting pines are exerting geographically variable selection on fungal populations (Hoeksema and Thompson 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Many studies suggest that microbial populations and communities are often structurally and genetically more diverse [67], [69], considering both type or strain richness and/or genetic diversity [68], than what can be explained by local host diversity [70]. Also the effectiveness of rhizobia, such as their ability to form nodules and their capacity to fix nitrogen, varies greatly within species, and naturally, between species [27], [58], [71], [72]; similar conclusions hold for the performance of mycorrhizal interactions [26], [65], [73]. This diversity amounts to a high variety of investment strategies; in other words, less mutualistic types coexist with more beneficial mutualists in natural communities [6], [19], [21], [22], [27], [34], [36], [71].…”
Section: Discussionmentioning
confidence: 84%
“…For example, many nutritional mutualisms, including mycorrhizal or rhizobial mutualisms [13], are highly beneficial for host plants as long as the resource provided (e.g., phosphorus, nitrogen, or copper) is absent from the environment, but can become harmful (implying that costs exceed benefits) when that resource no longer is a limiting factor [2], [38], [19], [76]. This not only underscores the importance of reactive strategies for modeling mutualism, but also offers one explanation for the spatial mosaic structures observed that involve different genotypes, as well as the different local coevolutionary states shaped by different local selective forces [45], [65], [77][79]. Our findings highlight that spatial environmental heterogeneity is not required for the creation of such mosaics, as the mechanisms unraveled here provide a testable alternative explanation of these empirical observations, even in the complete absence of spatial environmental heterogeneity.…”
Section: Discussionmentioning
confidence: 89%